2022
DOI: 10.1177/01634437221104709
|View full text |Cite
|
Sign up to set email alerts
|

Fostering intimacy on TikTok: a platform that ‘listens’ and ‘creates a safe space’

Abstract: This research explores how and why TikTok users from Turkey choose to make TikTok content. Drawing from the concept of polymedia and debates on digital connection and disconnection, which center on individuals’ choices whether to connect or detach from digital media based on the affordances they offer, the article highlights an affordance shaping users’ choices of media that have not received sufficient emphasis in these discussions: namely, the ability of a platform to foster intimacy. Based on qualitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Perceiving TikTok as a “safe” space on her mobile, where she could feel secluded and enjoy entertaining content, Jennifer’s description illustrates how her social media use involves the navigation between different emotional states, again highlighting social media as gateways to a portable mental space constantly at hand, used to transform everyday situations from pressing and uncomfortable to desirable experiences. Similar experiences of TikTok as a “safe space” have been explored by Şot (2022).…”
Section: Social Media As An Everyday Practicementioning
confidence: 81%
See 1 more Smart Citation
“…Perceiving TikTok as a “safe” space on her mobile, where she could feel secluded and enjoy entertaining content, Jennifer’s description illustrates how her social media use involves the navigation between different emotional states, again highlighting social media as gateways to a portable mental space constantly at hand, used to transform everyday situations from pressing and uncomfortable to desirable experiences. Similar experiences of TikTok as a “safe space” have been explored by Şot (2022).…”
Section: Social Media As An Everyday Practicementioning
confidence: 81%
“…On a more individual level, questions about how and why people use social media have been a focus within uses-and-gratifications research (e.g., Alhabash & Ma, 2017; Jung & Sundar, 2016; Whiting & Williams, 2013), a research tradition which is, nevertheless, of limited assistance for understanding how social media are experienced more deeply, within everyday contexts, where qualitative and ethnographic studies can provide further guidance. As an example of the latter, boyd’s (2014) extensive research on the “networked sociality” of American teenagers shows how adolescents use a range of social media to construct their identities, manage their social lives, and participate in public spaces, while illuminating the importance of social contexts such as school and family life for shaping their use (see also Bengtsson, 2006; Johansson, 2011; Lewis & West, 2009; Livingstone, 2008; Şot, 2022). In an ethnographic study of the impact of Facebook on the lives of ordinary people in Trinidad, Miller (2011), similarly, underlines geocultural context as key to understanding social media use; an aspect that has been explored further in comparative ethnographies (Costa, 2018; Miller et al, 2016).…”
Section: Social Media In Everyday Life: a Research Reviewmentioning
confidence: 99%
“…In other words, algorithmic affordances can play an important role in affecting users’ decisions and strategies about mental illness disclosure and the curated audience of disclosed content, thus managing the formation of social relationships among users. Moreover, algorithms that tailor the content audience effectively can help users find a safe place where only like-minded individuals gather without drawing unwanted attention, fostering intimacy with similar others (Şot, 2022). Building on this line of thinking, we would like to take one step further and discuss community building as an important need of mental health communities on an algorithm-mediated platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algorithm-mediated platforms recommend content mostly based on personal tastes, interests, and identities; hence, they do not require users to have any prior connections with each other (Karizat et al, 2021). Researchers further found that, because of the confidence in the algorithm’s interest-based recommendations, niche communities that were bound to like-minded individuals might thrive on algorithm-mediated platforms (Kang & Lou, 2022; Şot, 2022). However, it is worth noting that the content community built by algorithms is also distinctly different from other SNS platforms such that communication between users is less frequent and replaced by users’ interactions with algorithms (Bhandari & Bimo, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, with the surge in video telecommunication technologies and covid19 pandemic, observing other people "on-screen" has become a major way people obtain information and connect with other people. For instance, people watch news from televisions and online news channels (43), take classes and have meetings via video conferencing (44,45), and share videos of themselves and watch videos of others on social media such as YouTube and TikTok (46). The stimuli we use in the present research capture this important everyday life context, portraying participants freely talking about significant events in their life (47).…”
Section: Introductionmentioning
confidence: 99%